PERANCANGAN SISTEM PAKAR UNTUK IDENTIFIKASI GANGGUAN HAMA DAN PENYAKIT PADI (ORYZA SATIVA) MENGGUNAKAN METODE FORWARD CHAINING - Agusman Agusman; Ilyas Ilyas (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2020)
With the development of science and technology, this pest and rice disease information can not only be obtained through consultation with experts, but also can be known through an expert system. This will help the consumer to facilitate in consultation on diseases and pests of rice plants. The results obtained from this study are: This system can help facilitate the community in detecting damage to his crops caused by pests and diseases. Able to provide diagnostic results based on the symptoms found. Implementation of forward chaining method is able to answer the problem of society in analyzing the type of disease or pest causing damage to rice plant based on the collected knowledge